Safety and Health Management Implementation - Muhamad Abdul Jumali; Yitno Utomo; Rusdiyantoro (Tibuana, 2022)
The development of industry by empowering high technology is accompanied by an increase in players and technology users in the industrial era and globalization. So it is necessary to pay attention to work safety as an effort to improve human resources in the field of Occupational Safety and Health Management System. The theme of Occupational Safety and Health Management System is very interesting to study and continue to develop. So the purpose of this research is to know the implementation of Occupational Safety and Health Management System in accordance with the Standard Operating Procedure and to know the use of Personal Protective Equipment for employees in the maintenance department of a shoe-making company according to the rules and rules of Occupational Safety and Health Management System. The research method used is comparative quantitative research (comparing quantitatively). The research subjects were employees in the maintenance department of a shoe-making company which collected 60 people. The results of this study indicate that the Post-Test value > from the Pre-Test results. Therefore, the implementation of the Health and Safety Management System in the maintenance department has been implemented or in accordance with standart operation procedure and policies of a shoe-making company.